Natural cycle increases the live-birth rate compared with hormone replacement treatment for frozen-thawed single euploid blastocyst transfer - Li, Xiaofang; Gao, Yan’e; Shi, Juanzi; Shi, Wenhao; Bai, Haiyan (Frontiers in Endocrinology, 2022)
Background: A number of studies have compared the clinical outcomes between the two endometrial preparation methods: natural cycles (NC) and hormone replacement treatment (HRT) before frozen embryo transfer, but the results were conflicting. In order to mitigate the potential effect of embryo per se, several researchers have worked on this subject for euploid blastocysts transfer, but the results were still inconsistent. Therefore, the present study was aim to investigate the clinical outcomes between HRT and NC for autologous single vitrified-warmed euploid blastocyst transfer based on our data. Methods: Five hundred and ninety-eight frozen-thawed single euploid blastocyst transfer cycles in the assisted reproductive center of Northwest Women's and Children's Hospital from January, 2014 to May, 2021 were retrospectively analyzed. Women were stratified into NC (n = 125) or HRT (n = 473) group according to the patient’s preference and physician’s guidance. Multivariate regression models and subgroup analysis were constructed to analyze the association between endometrial preparation and live birth. Results: Women in NC group had higher live birth rate (68.80% versus 58.35%, P = 0.034) and lower risk of total pregnancy loss (8.51% versus 21.14%, P = 0.005) when compared with women in the HRT group. Biochemical pregnancy rate (75.20% versus 74.00%, P = 0.784) and clinical pregnancy rate (74.40% versus 69.98%, P = 0.334) were similar between the two groups (NC versus HRT). NC was associated with an increased odds of live birth compared with HRT by different multivariable analysis models (Model 1: adjusted odds ratio [aOR], 95% confidence interval [CI]: 0.57, 0.36 - 0.90; Model 2: aOR, 95%CI: 0.57, 0.35 - 0.92). And the increased chance of live birth in the NC group was found in all subgroups. No major obstetrical complication and two malformation livebirths were reported. Conclusions: In women undergoing single euploid frozen blastocyst transfers, NC group was associated with lower pregnancy loss rate and ultimately higher live birth rate than HRT group. Although HRT is convenient for both clinicians and patients, the lower live birth rate should be taken into account and NC might be the first choice of endometrial preparation method.